Hubungan Antara Kemampuan Pengelolaan Kelas Guru dengan Motivasi Belajar Siswa di MAS Plus Al-Ulum - Reihan Kamila Hasri (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
The research was carried out against the background that low learning motivation can be caused by various factors, including the teacher's lack of ability to manage the learning process. In this way, this research aims to find out whether there is a relationship between teachers' classroom management abilities and students' learning motivation at MAS Plus Al-Ulum. The research methodology uses a correlational approach. with a population of 140 students. If the number of subjects is large, between 10-15% or 20-25% or more can be taken. Sample = 28% The data collection technique in this research uses a research instrument, namely a scale. The scale validity data processing tool is implemented using content validity. The results of this research show that the coefficient between the variables classroom management ability (X) and student learning motivation (Y) at MAS Plus Al-Ulum is 0.39. Through the t test carried out, the calculated t value was 2.636, while the t table value was 2.02. This indicates that there is a positive and significant relationship between the variable class management ability (X) and student learning motivation (Y). This relationship is linear and can be predicted using the regression line Ŷ = 67.18 + 0.29.